2006
DOI: 10.4161/cbt.5.9.2950
|View full text |Cite
|
Sign up to set email alerts
|

Pheophorbide a, an active compound isolated fromScutellaria barbata, possesses photodynamic activities by inducing apoptosis in human hepatocellular carcinoma

Abstract: Photodynamic therapy (PDT) is an effective treatment for cancer by inducing apoptosis or necrosis in the target cells. Pheophorbide a (Pa), a chlorophyll derivative, is a photosensitzier which can induce significant anti-proliferative effects in a number of human cancer cell lines. This study investigated the action mechanism of Pa-mediated photodynamic therapy (Pa-PDT) on the human hepatocellular carcinoma, Hep3B cells. Pa-PDT significantly inhibited the growth of Hep3B cells with an IC50 value of 1.5 microM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 0 publications
5
80
0
Order By: Relevance
“…This observation suggests that P-a was concentrated in the mitochondria, consistent with data summarized in Fig. 2A,B, and literature reports (MacDonald et al, 1999;Tang et al, 2006).…”
supporting
confidence: 80%
“…This observation suggests that P-a was concentrated in the mitochondria, consistent with data summarized in Fig. 2A,B, and literature reports (MacDonald et al, 1999;Tang et al, 2006).…”
supporting
confidence: 80%
“…The purity of the compound was tested by HPLC-DAD. The structure, as shown in Figure 1 (27), 108(100), 91(33), 77 (27), 65 (14), 53 (16), 41 (27).…”
Section: Methodsmentioning
confidence: 99%
“…We have isolated and identified several chemical extracts and pure compounds from Chinese medicine with anti-hepatoma, anti-multidrug resistant hepatoma and antihepatitis viral effects. [16][17][18][19] Essential oil of Ezhu and it active ingredients have been widely used for treatment of malignant tumors in China. 4,5 Furanodiene, an ingredient from Ezhu oil, has been identified to have protective effects against D-galactosamine/ lipopolysaccharide/TNFa induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…The recent study by Tang et al 20 demonstrated that growth of Hep3B cellsderived xenograft tumors in nude mice were significantly inhibited by PDT treatment. 21 As most of the HCC cases in China derive from chronic HBV infection, the effectiveness of PDT in Hep3B cells-derived xenograft tumors would imply a potential usefulness of PDT in the treatment of chronic HBV infection related HCC. The use of extracted Chinese herbal medicine Pheophorbide a (Pa) in this study as a photosensitizer also has some practical implications, given that Chinese medicinal herbs are widely available, less toxic, and relativey less costly.…”
mentioning
confidence: 99%
“…2 As a photosensitizer, Pa has been shown to inhibit the growth of many human cancers including Jurkat leukemia, colonic cancer, pancreatic carcinoma, and HCC. [27][28][29][30] Tang et al 21 have showed that Pa could enhance the efficacy of PDT for HCC, very likely due to its antiproliferative and pro-apoptotic effect. The induction of apoptosis by Pa was through intrinsic pathway.…”
mentioning
confidence: 99%